Nonisothermal analysis of a couple stress fluid in blade coating process. Issue 6 (12th March 2020) - Mughees, Muhammad; Sajid, Muhammad; Ali, Nasir; Shahzad, Hasan
Abstract: In this paper, a nonisothermal analysis for the process of blade coating of an incompressible couple stress fluid is presented using both plane and exponential coaters. The governing system is simplified using lubrication approximation theory (LAT). The interesting quantities from engineering point of view like normalized pressure, maximum pressure, pressure gradient, velocity, and effects of involved parameters on temperature distribution, which influence the coating process are evaluated. It is observed that pressure is at maximum near the edge of the blade whereas fluid velocity and temperature are at maximum near the substrate. An increasing couple stress parameter increases the load and decreases the coating thickness. It is worth mentioning that load and pressure are the most significant outcomes of the present exertion as these two physical quantities ensure thickness and the quality of coating.